Implementation of Nursing Center in Improving the Quality of Nursing Higher Education in the Era of Society 5.0: Systematic Review - Mira Asmirajanti; Antia Antia; Ratna Dewi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Nursing higher education is an institution that plays an important role in producing quality nurses, able to compete in the era of Society 5.0. Students need to be given training in educational laboratories. Nursing centers are integrated management in research, education, and nursing practice which are a place to produce competent nurses, although their existence can still be counted on. This study aims to determine the implementation of orphanages in improving the quality of higher education in nursing in the Era of Society 5.0. This study used a Systematic Literature Review of undergraduate data sources Pubmed, ScienceDirect, and Google, PICO search strategies, and full articles in pdf. The search results obtained 14586 articles from 2012 -2022, after reviewing the titles and abstracts, 60 articles were selected. Selected articles are assessed for feasibility, categorized, and adapted to the research theme. 24 articles were used for research and included in the PRISMA flowchart. Nursing Higher Education must carry out a transformation to improve the quality of service. The nursing center is a facility for learning, research, and student practice on evidence-based practices. Students have the necessary competencies to work effectively and efficiently, confidently, and use technology. Improving the quality of education is highly dependent on the learning process, operational management, and information systems. Virtual reality is a technological innovation used for student practice. Accreditation is carried out to improve the quality of education. Government and organizational support are needed to monitor and assess the application of professional standards and ethics.